A Aprendizagem cooperativa como estratégia metodológica no ensino da matemática no ensino médio - Penha, Rodolfo Sena (2017)
The present research is about the teaching of mathematics, aiming to describe the use of Cooperative Learning as a methodological strategy of teaching mathematics in the first year of high school in the State School of Professional Education Prof.ª Alda Façanha, in the period referring to the school year the questions that guided the implementation of Cooperative Learning were: What to do and how to improve student learning outcomes in math in internal and external assessments? What strategies are used in the classroom to modify the adverse scenario? The methodology of the present research is characterized by being descriptive, bibliographical and field. The research technique used was the implementation of Cooperative Learning in the school as teaching and learning methodology, with the purpose of describing and improving the results obtained by the school in external evaluations. The application of Cooperative Learning took place in a total of four (04) weekly classes lasting 50 minutes each, during three bimetals and had the participation of 180 students in 4 groups of 45 students, all of the first year of integrated high school to the technical courses of buildings, lodging, computer networks and electrotechnology. The methodology was implemented in three phases: preimplementation, implementation and post-implementation, which lasted approximately eight months. In each of these phases there were a series of planning and activities carried out with the teachers and students aiming at an autonomy and consequent student protagonist. The results of the study demonstrate that the students presented very significant results of improving learning, developed relevant social skills, particularly mutual respect between students and between teachers and students.